Dampak Pandemi Covid-19 Terhadap Perkembangan Ekonomi Dan Sosial Keagamaan Pada Masyarakat Pesisir - Rahmat Sulistio (Jurnal Abdi Mas Adzkia, 2022)
AbstractThis study examines the impact of the Covid-19 pandemic on the economic and socio-religious development of coastal communities in Pulau Simardan Village, Datuk Bandar Timur District, Tanjungbalai.  The research method applied in this study is a descriptive survey method with qualitative data analysis.  The data collection techniques used were observation, interviews, literature studies and documentation.  This study aims to obtain information about the impact of the Covid-19 pandemic related to the economic and socio-religious developments that occur in coastal communities.  The impact of the Covid-19 pandemic can be seen in the decline in people's income figures such as the decline in fish prices and reduced income for traders.  On the other hand, socio-religious activities also have an impact by limiting every religious activity and keeping a distance in worship and trying to do all activities from home.